Columbia social work review - Columbia University. School of Social Work (Columbia University School of Social Work, 2010)
The Columbia Social Work Review (formerly the Columbia University Journal of Student Social Work) is an annual peer-reviewed journal for students in the field of social work to share their research, experiences and views with faculty, fellow students, and the wider scholarly community. The Review strives to enrich the scholarly nature of our school by providing a forum for the exchange of innovative ideas from the perspective of social work students, and giving students the opportunity to be published in an academic journal as master's students.
Keywords: Social service : Periodicals; Social service